Voter Targeting Online in Comparative Perspectives: Political Party Websites in the 2008/2009 and 2013 Austrian and German Election Campaigns. Issue 3 (2nd July 2020) - Russmann, Uta
Abstract : The web allows political parties to segment and microtarget specific groups of voters. This paper seeks to measure voter targeting online focusing on catch-all parties and client parties' websites during the 2008 and 2013 Austrian general elections and the 2009 and 2013 German federal elections. Thereby, this comparative longitudinal analysis also aims to provide insights into the development process of political targeting strategies. From a theoretical perspective, catch-all parties try to appeal to a diverse spectrum of potential voters, whereas client parties are aiming at a more specific type of voter. The results of the content analysis show that (a) information and services on parties' websites increasingly focus on addressing the general public and (b) differences between catch-all and client parties have been reduced between campaigns.